Multi-objective assessment of conservation measures for the European eel (Anguilla anguilla): an application to the Camargue lagoons - Bevacqua, Daniele; Melià, Paco; Crivelli, Alain J.; Gatto, Marino; De Leo, Giulio A. (ICES Journal of Marine Science, 2007)
<qd> Bevacqua, D., Melià, P., Crivelli, A. J., Gatto, M., and De Leo, G. A. 2007. Multi-objective assessment of conservation measures for the European eel ( Anguilla anguilla ): an application to the Carmargue lagoons – ICES Journal of Marine Science, 64. </qd>The European eel ( Anguilla anguilla ) stock has declined since the early 1970s and is currently considered to be outside safe biological limits. The European Commission has proposed a regulation (COM 2005/472 final) to establish measures for the recovery of the stock, with the aim of achieving an escapement to the sea of 40% of the adult eel biomass (with respect to undisturbed conditions) from each river basin. The proposed regulation imposes an effective reduction of fishing activities until implementation of an approved eel management plan. We use a demographic model, explicitly accounting for age, length, and sex structure, and important features of the continental phase of eel life cycle, to assess the effectiveness of the proposed regulation. We explore alternative management options with reference to the Camargue (southern France) eel population. Using multi-criteria methods, we compare different fishing policies with respect to two potentially conflicting objectives: preserving a sufficient spawner escapement and guaranteeing an acceptable harvest to fishers. We show that the current fishery is inefficient and that appropriate management policies (such as limiting the fishing season and increasing the mesh size of fishing gear) are likely to have a doubly positive effect, by achieving the conservation target of the regulation and increasing fisher revenues.